2009
DOI: 10.1681/asn.2009010061
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble VEGF Receptor sFlt1 Contributes to Endothelial Dysfunction in CKD

Abstract: Endothelial dysfunction contributes to the increased cardiovascular risk that accompanies CKD. We hypothesized that the soluble VEGF receptor 1 (sFlt-1), a VEGF antagonist, plays a role in endothelial dysfunction and decreased angiogenesis in CKD. We enrolled 130 patients with CKD stages 3 to 5 and 56 age-and gender-matched control patients. Plasma sFlt-1 levels were higher in patients with CKD and, after multivariate regression analyses, exclusively associated with renal function and levels of vWF, a marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 43 publications
(29 reference statements)
9
150
0
Order By: Relevance
“…3,5,6,35,36 H 2 S is known for its proangiogenic, antihypertensive, and organ protective properties. 28,37,38 In this study, we investigated the effects of exogenously administrated H 2 S in a rat model for severe endothelial dysfunction, induced by overexpression of sFlt1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,6,35,36 H 2 S is known for its proangiogenic, antihypertensive, and organ protective properties. 28,37,38 In this study, we investigated the effects of exogenously administrated H 2 S in a rat model for severe endothelial dysfunction, induced by overexpression of sFlt1.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In preeclampsia, a consistent line of evidence has shown that increased sFlt1 is one of the major contributors to the development of hypertension and proteinuria. [4][5][6][7] sFlt1 is a splice variant of the vascular endothelial growth factor (VEGF) receptor lacking the transmembrane and cytoplasmic domains and acts as a powerful antagonist of VEGF, thereby inhibiting VEGF signaling in the vasculature.…”
mentioning
confidence: 99%
“…In a previous study, Di Marco, et al also reported that sFlt-1 levels were independently associated with renal dysfunction. 29) In experimental animal models, exogenous administration of sFlt-1 to either pregnant or nonpregnant animals was found to induce widespread endothelial dysfunction, hypertension, and renal dysfunction. 10,30) These data suggest that the antiangiogenic effects of sFlt-1 may affect compensatory angiogenesis in diseased kidneys and failing hearts.…”
Section: Discussionmentioning
confidence: 99%
“…17 These angiogenesis inhibitors are released under inflammatory state. 18,19 These circulating proteins have been shown to have pathogenetic roles in hypertension in preeclampsia, 20 in human chronic kidney disease, 21 coronary artery disease 22 and in animal models of hypertension. 23,24 However, none of the studies have examined the relationship between endothelial dysfunction and hypertension in relationship to hypoxia exposure in OSA patients.…”
Section: Introductionmentioning
confidence: 99%